Association of Anthropometric Profiles with Triglyceide/High-Density Lipoprotein Ratios in Adult Islamic Boarding School Students - Batubara, Astriana Marta; Tsani, A. Fahmy Arif; Utomo, Astika Widy; Syauqy, Ahmad (Jurnal Gizi dan Pangan, 2023)
The aim of this study was to analyze the relationship between anthropometric profiles and Triglyceide/High-Density Lipoprotein (TG/HDL-C) ratio in adult Islamic boarding school students. A cross-sectional study was conducted on 83 Islamic boarding school students, aged 19 to 23 years, selected using a consecutive sampling design. Anthropometric measurements consisted of Waist Circumference (WC), Waist-to-Hip Ratio (WHR), and Skinfold Thickness (SFT). There were 45.8% students who had high TG/HDL-C ratio, WC (p<0.001; r=0.379) and WHR (p<0,001; r=0.455). The respondents' waist circumference and waist-to-hip ratio were positively associated with TG/HDL-C ratio.